Low-temperature synthesis of superparamagnetic Zn0.8Ni0.2Fe2O4 ferrite nanoparticles - Anh, Luong Thi Quynh; Dan, Nguyen Van; Nghiep, Do Minh (Vietnam Journal of Science and Technology, 2018)
The crystalline nanoparticles of Ni0.2Zn0.8Fe2O4 ferrite were synthesized by chemical co-precipitation with precursor concentration of 0.1M, then modified by 0.25M solution of oleic acid in pentanol, finally heated at temperatures 120, 140, 160 and 180oC for 6h in autoclave. The XRD, EDS and TEM confirmed that all of samples are crystalline and their particle size are 6, 6.5, 7 and 8 nm. The magnetic properties showed that the coercive force, the remanence of samples are about zero, the saturation magnetization Ms has values from 14.20 to 27.12 emu/g.